2008
DOI: 10.1007/s10452-008-9175-x
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variations of microphytoplankton assemblages and environmental variables in the coastal zone of Bozcaada Island in the Aegean Sea (NE Mediterranean Sea)

Abstract: Seasonal changes in the microphytoplankton assemblages were examined in the coastal zone of Bozcaada Island with regard to some major physical and chemical variables. Samples were collected from May 2000 to December 2001 at four stations. A total of 108 dinoflagellates, 102 diatoms, 1 chrysophycean, 3 dictyochophycean, and 1 prasinophycean species were identified and quantified during the study period. Diatoms and dinoflagellates were the most important in terms of species number and abundance. The maximum val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
18

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 37 publications
1
12
0
18
Order By: Relevance
“…Intense deep convection events were reported in 2005, 2006winters (Civitarese et al, 2010Bensi et al, 2013) when the area is classed as "Bloom #5". Less intense convection, reported for the winters 2000, 2008, 2009(Gacic et al, 2002Bensi et al, 2013), seems to be associated with "Intermediate #4" or "No Bloom #5" regimes.…”
Section: "Intermittently #4" Trophic Regimementioning
confidence: 73%
See 1 more Smart Citation
“…Intense deep convection events were reported in 2005, 2006winters (Civitarese et al, 2010Bensi et al, 2013) when the area is classed as "Bloom #5". Less intense convection, reported for the winters 2000, 2008, 2009(Gacic et al, 2002Bensi et al, 2013), seems to be associated with "Intermediate #4" or "No Bloom #5" regimes.…”
Section: "Intermittently #4" Trophic Regimementioning
confidence: 73%
“…In the North Aegean Sea, the influence of the rivers and of the Black Sea Water on the phytoplankton productivity has been recently confirmed (Tsiaras et al, 2012. The load of nutrients in these areas by the river and/or the Black Sea Water in late spring (in May, Balkis, 2009) could also explain the occurrence of the "Anomalous #2" trophic regime, which presents a "plateau" in May, instead of the "No Bloom #2" trophic regime. At an interannual level, however, no trends or correlations have been identified.…”
Section: The "No Bloom" Trophic Regimesmentioning
confidence: 91%
“…Some previous studies carried out in the eastern Mediterranean and Aegean Seas have shown that this region has oligotrophic characteristics (Azov 1991;Krom et al, 1991;Ignatiades et al, 2002;Turley et al, 2000;Balkis, 2009).…”
Section: Discussionmentioning
confidence: 90%
“…A number of studies on phytoplankton communities, dealing mainly with taxonomy, ecology and biomass distribution, have been carried out in the north-eastern Mediterranean Sea (Kideyş et al, 1989;Eker & Kideyş, 2000, Polat et al, 2000Polat & Işik, 2002;Polat, 2002;Polat & Piner, 2002a;Polat & Piner, 2002b;Polat et al, 2005;Eker-Develi et al, 2006;Polat, 2007;Polat & Koray, 2007;Balkis, 2009;Ozman-Say & Balkis, 2012). The Datça-Bozburun Specially Protected Area is one of thirteen specially protected areas in Turkey.…”
Section: Introductionmentioning
confidence: 99%
“…Table 3, were at eutrophic range in February (0.47-13.09 μM) and at mesotrophic range in July (0.30-2.28 μM) according to criteria provided for Aegean and Mediterranean coastal waters (Balkıs, 2009;Redfield, 1958). PO4…”
Section: E Esenmentioning
confidence: 99%